Urbanization and symptomatic malaria in relation to retroviral screening (2008)
A descriptive cross-section analysis of five hundred patients who were symptomatically diagnosed of malaria in three locations: Saki (peri-urban), Ibadan (urban) and Lagos (highly urbanized) were recruited for this study using a well structured questionnaire between September 2005 and June 2006. The prevalence of both malaria and HIV infections were higher in Peri-Urban town than the other two locations. We observed that 80% were HIV positive in Saki. 20% in Ibadan and 37.1 % in Lagos. Our data indicated that 74% were malaria positive in Saki, 87% in Lagos and 24% in Ibadan. The percentage of co-infection in Saki, Logos and Ibadan were 69%, 16% and 14.3% respectively. The high prevalence of coinfection in the two cross-border locations (Saki and Lagos) is suggestive of a high correlation between clinical symptomatic malaria and HIV infection with respect to cross border transmission of the two infections . This paper suggests that government should make provision to establish sentinels for screening immigrants.